Experimental investigation, techno-economic analysis and environmental impact of bioethanol production from banana stem - Hossain N.; Razali A.N.; Mahlia T.M.I.; Chowdhury T.; Chowdhury H.; Ong H.C.; Shamsuddin A.H.; Silitonga A.S. (MDPI AG, 2023)
Application programs; Bioethanol; Costs; Distillation; Economic analysis; Electric power generation; Environmental impact; Ethanol; Fermentation; Fruits; Glucose; Operating costs; Yeast; Acid hydrolysis; Banana stem; Bio-ethanol production; Environmental analysis; Homer softwares; Techno-economics; Yeast fermentation; Enzymatic hydrolysis